ChemInform Abstract: A Two‐Step Sequence to Ethyl α‐Fluorocyclopropanecarboxylates Through MIRC Reaction of Ethyl Dichloroacetate and Highly Regioselective Fluorination. Issue 16 (22nd April 2014) - Zhang, Min; Gong, Yuefa; Wang, Weizhou
Abstract The two‐step sequence yields monofluorinated cyclopropane derivatives which are of pharmaceutical interest due to their biological activities.